Pocket parks. Public space, public life, urban practices - Krupa-Ławrynowicz, Aleksandra; Orszulak-Dudkowska, Katarzyna (A mosaic city: The culture-oriented description, 2023)
The article discusses the main assumptions and cultural and social parameters of urban public space. The example under analysis are city parks, with particular emphasis on the idea of pocket parks, which in contemporary urban planning are a response to the shortage of green areas in large, densely built-up cities. A short historical reconstruction of the city – nature – man relationship is accompanied by a description of selected urban projects and an attempt to place them in social contexts and the idea of the “right to the city”.